Exploring Customer Journeys in the Context of Dentistry: A Case Study - Bhaven Modha (MDPI AG, 2023)
This case study aims to explore how customer journey concepts can apply to a hypothetical scenario, centring on a patient (customer persona) within the dentistry arena, and with a particular focus on special care dentistry. As an educational exercise, this paper may inform dental and allied professionals on how aspects of the customer journey notion may be embedded into their own practices, so that patient-centricity might be better optimised. The hypothetical scenario considers the organisational context, customer persona, contemporary customer purchase decision-making models, and marketing approaches. These components are used to create a customer journey map to help visualise and identify the varying customer-business interactions. The customer journey, focussing on the awareness, initial consideration, active evaluation, pre-purchase, purchase and post-purchase stages, is then conceptually analysed. The analyses reveal that there are areas of friction, attributable to numerous factors. The case study recommends that by introducing digitalisation and omnichannel marketing, alongside existing internally generated and multi-channel marketing approaches, considerable improvements may be achievable. As the patient technology landscape becomes more digital and dental organisations face fiercer competition, dental care providers relying on traditional marketing approaches may well need to adapt and introduce innovative, yet cost-effective digitalisation and omnichannel marketing approaches. Nevertheless, dental care providers, and dental and allied professionals must uphold an underlying duty of care, ensuring that all practises are legal, decent, honest, truthful, and above all ethical.